Iktikad Baik dalam Pelaksanaan Kontrak: Super Eminent Principle yang Memerlukan Pengertian dan Tolok Ukur Objektif - Ridwan Khaiarandy (Fakultas Hukum Universitas Islam Indonesia, 2007)
This study focuses two legal issues deal to the meaning and legal tests of good faith on contract performance. Using the descriptive analysis with normative juridical approach, and library data, this study reveals: First of all, the meaning of good faith on contract performance is not universal, but there is a tendency its meaning refers to objective good faith. Lastly, legal test of that good faith uses objective tests, namely reasonableness and equity.